Privatization in the presence of foreign competition and strategic policies - Dijkstra, Bouwe; Mathew, Anuj; Mukherjee, Arijit (Springer Verlag, 2014)
Recent evidence shows that developing and transition economies are increasingly privatizing their public firms and also experiencing rapid growth of inward foreign direct investment (FDI). In an international mixed oligopoly with strategic tax/subsidy policies, we analyze the interaction between privatization and FDI. We find that the incentive for FDI increases with privatization. However, the possibility of FDI reduces the degree of privatization. Our paper shows that FDI policies reducing the fixed-cost of undertaking FDI may need to complement the privatization policies to attract FDI and to improve domestic welfare.